Comparasion Of Visual Outcomes Post Small Incision Cataract Surgery With Phacoemulsification At Dustira Hospital 2017-2022 - Lukmana Lokarjana; Arini Ghaisa Atsari; Natashya Iasha Bahtiar (Sean Institute, 2025)
The eye is a human visual instrument that functions to provide information visually to the brain. One of the vision disorders that often occurs is cataracts. Global data on visual impairment in 2010 stated that cataracts are one of the most common visual impairment disorders worldwide (33%). Based on Riskesdas in 2018, the prevalence rate of cataracts in Indonesia is 1.5%. Treatment of eyes diagnosed with cataracts can be done with several surgical techniques including SICS and phacoemulsification. The purpose of this research is to determine the comparison of visual outcomes post surgery small incision cataract surgery with phacoemulsification at Dustira Hospital in 2017-2022. This research is an analytical descriptive research using retrospective cross sectional design. The sample of this study was patients diagnosed with cataracts who underwent surgery using SICS techniques and phacoemulsification in 2017-2022 at the Eye Poly of Dustira Hospital. The selection of research samples uses total sampling methods and those in accordance with the inclusion criteria and exclusion criteria that have been determined. The data were analyzed using Man Whitney's non-parametric hypothesis test. The results of this study obtained the results of visual examination of post-cataract surgery outcomes on the SICS technique and phacoemulsification techniques had p-values on the control day 1 p = 0.019, day 7 p = 0.008 and day 30 p = 0.046. So it can be concluded that there is a significant difference in visual outcomes after cataract surgery using the SICS technique with phacoemulsification at Dustira Hospital in 2017-2022.